(untitled) (Journal of Tikapur Multiple Campus, 2017)
The goal of this research is to investigate the level of students’ achievement in science and how can we make it easy and competent by taking the feedback from NASA, TIMMS and PISA to develop scientific literacy in Nepal. It provides the criteria to judge progress towards the science education vision of scientific literacy for all. Stratified random sampling was done to pursue this study to select the sampled schools and the students. The sample size for this assessment was 44067 students, including 48% boys and 52% girls from the 1199 randomly selected schools of 28 sample districts, representing each strata of population. The results of the international assessment like Trends in International Mathematics and Science Study (TIMSS) and Program for International Student Assessment (PISA) is compared with the result of this study. The average achievement score in science is 41%, which is very low in comparison to international tests and standards.Nepal government need to improve the condition of scientific literacy through the medium of science education.